Supporting children facing a parent's cancer diagnosis: a systematic review of children's psychosocial needs and existing interventions. (18th January 2016) - Ellis, S.J.; Wakefield, C.E.; Antill, G.; Burns, M.; Patterson, P.
Abstract : This review aimed to (1) summarise the psychosocial needs of children/adolescents (0–18 years) with a parent with cancer across the illness trajectory (diagnosis to bereavement) and (2) evaluate existing interventions for this population. Medline, CINAHL, PsychInfo, EMBASE and Social Work Abstracts were systematically searched for articles published from 1985 to 2015. Of 98 full text articles retrieved, 12 reported on children's psychosocial needs, and 12 intervention studies were identified. Each article was appraised in accordance with the Mixed Method Appraisal Tool. Three factors emerged as critical to consider in future intervention development: (1) Children need age‐appropriate information about their parent's cancer; (2) Children require support communicating with parents, family members and health professionals and (3) Children need an environment where they feel comfortable sharing positive/negative emotions and can have their experiences normalised among peers. All intervention studies reported at least one positive outcome, however, only five reported significant improvements in child/family functioning based on validated quantitative measure/s. Variability in study design and quality, combined with considerable heterogeneity in intervention characteristics and outcome variables limited the conclusions, which could be drawn. Therefore, further carefully designed and scientifically evaluated interventions for children facing a parent's cancer diagnosis are clearly warranted.